Metabolomics of Clinical Poisoning by Aconitum Alkaloids Using Derivatization LC-MS - Zhang, Yida; Bian, Xiqing; Yang, Jing; Wu, Haiying; Wu, Jian-Lin; Li, Na (Frontiers in Pharmacology, 2019)
The root of Aconitum kusnezoffii (Caowu in Chinese, CW) is not only commonly used as a traditional Chinese medicine (TCM), but also served as a tonic in China. Due to its high toxicity, clinical poisoning cases induced by CW have frequently been reported. However, the mechanism is still unclear. In this study, Aconitum alkaloids and altered endogenous metabolites in CW poisoning patients were investigated to elucidate the possible intoxication mechanism. Eighteen alkaloids, including 6 toxic diester diterpenoid alkaloids (DDAs), were determined from the sera of patients. At the same time, 5-(diisopropylamino)amylamine (DIAAA) derivatization-ultrahigh performance liquid chromatography- quadrupole-time of flight mass spectrometry (UHPLC-Q-TOF/MS) approach was applied in the metabolomics analysis to find much more carboxyl-containing metabolites (CCMs), which are the essential components for life and critical to elucidate the mechanism of toxicity. As a result, 32 altered metabolites after poisoning were identified. Among them, hydroxyeicosatetraenoic acids (HETEs) and some dicarboxylic acids were first found to be related to Aconitum alkaloids toxicity. Finally, biological pathway analysis indicated that the significantly changed metabolites were primarily involved in amino acid metabolism, TCA cycle, fatty acid metabolism, pyruvate metabolism, arachidonic acid metabolism, sphingolipid metabolism and so on. These results not only can provide more information on the mechanism of CW intoxication but also help the clinical diagnosis of CW poisoning.